Urinary incontinence following successful closure of obstetric vesicovaginal fistula repair in Southern Ethiopia - Shimelis Tadesse; Desta Mekete; Shambel Negese; Dereje Zeleke Belachew; Galana Takele Namara (BMC, 2024)
Abstract Background Urinary incontinence (UI) after successful closure of obstetric vesicovaginal fistula (VVF) repair is a widely recognized public health problem. However, there is insufficient research evaluating the factors associated with UI after successful obstetric VVF repair in Ethiopia. Objectives The main aim of this study was to assess the magnitude and associated factors of UI following the successful closure of obstetric VVF repair at the Yirgalem Hamlin Fistula Center in the Sidama region of southern Ethiopia. Methods A retrospective cross-sectional analytical study was performed on patients who underwent obstetric VVF repair at the Yirgalem Hamlin Fistula Center between 2016 and 2020. The data were collected from September to October 2021. EPI Data Version 3.1 and SPSS Version 25.0 were used for data entry and analysis. A multivariable binary logistic regression model was used for all variables significant in the bivariate binary logistic analysis to determine the association between the independent variables and outcome variables. The data are presented in tables and figures. Variables with a p-value < 0.05 were considered to be statistically associated with the study outcome. Results In total, 499 study subjects were included. The magnitude of UI after successful closure of obstetric VVF repair was 23.25%. A Goh type 4 fistula (AOR = 4.289; 95% CI 1.431, 12.852), a fistula size > 3 cm (AOR = 8.855; 95% CI 4.786, 16.382), a partially damaged urethra (AOR = 2.810; 95% CI 1.441, 5.479), and a completely destroyed urethra (AOR = 5.829; 95% CI 2.094, 16.228) were found to be significantly associated factors with the outcome variable. Conclusions Nearly one in four patients who had successful closure of obstetric VVF repair at the Yirgalem Hamlin fistula center had UI, which is above the WHO recommendations. The presence of a Goh type 4 fistula, large fistula size, and damaged urethral status significantly affect the presence of UI. Therefore, interventions are necessary to prevent and manage UI among patients who underwent obstetric VVF repair and had a closed fistula.